Pengaruh Application Quality dan Competitive Price terhadap Online Repurchase Intention pada Pengguna Aplikasi NusaTrip di Indonesia - Azzahra, Fahira; Widjajanta, Bambang; Lisnawati, Lisnawati (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2025)
This study aims to determine the influence of application quality and competitive price on online repurchase intention on NusaTrip application users. The type of research used is descriptive and verificative with a quantitative approach. The sample used in this study amounted to 350 respondent. The data obtained were processed statistically using the Structural Equation Modeling (SEM) method. The results of this study show that application quality and competitive price have a positive and significant influence on online repurchase intention. This is evidenced by the C.R. value being greater than 1,967 and the P value being less than 0,05. This statement can be assumed that the better the company pays attention to application quality and competitive price, the better the online repurchase intention that appears in consumers for the company.